Intervention by Separation and Reunification of Victims of Munchausen Syndrome by Proxy - Tiara Paramita; Adrianus Eliasta Meliala (Universitas Budi Luhur, 2021)
This study aims to analyze the impact of the intervention method by separating and reunifications children as victims of Munchausen Syndrome by Proxy against their parents as perpetrators of Munchausen Syndrome by Proxy. The subjects of this study were 9 expert figures with different backgrounds and several previous research journals as references. This research uses interpretative analysis by using an unstructured interview method and journal review for secondary data. After the data is collected completely and thoroughly, both from primary and secondary data collection, the data can be grouped or adjusted according to the type of data obtained from interviews with research subjects and previous research based on the journals. The results showed that the separation intervention is still one of the intervention methods used for victims of child abuse. However, this intervention can also cause deep psychological wounds in children due to being separated from their parents, where the trauma from the separation will greatly affect the psychological development of children in terms of their trust in others. Apart from that, reunification is still very possible, but the possibility of repeated acts of violence is also quite high. Continued and prolonged counseling is needed to minimize these negative impacts however, this follow-up step is still difficult to do, especially in Indonesia due to the lack of human resources from related institutions or agencies.